Effect of Baccharis genistelloides (carqueja) ethanol extract on 1,2-dimethylhydrazine-induced rodent’s colon cancer - Justil, Hugo (2010)
Introduction: Baccharis genistelloides leaves ethanol extract may reduce gastric cancer development and is an oxidative stress marker. Objectives: To determine the chemoprotector efficacy of Baccharis genistelloides (EEBG) leaves ethanol extract in 1,2-dimethylhydrazine (DMH)-induced colon cancer in male rats. Design: Experimental. Setting: Pharmacology Laboratory, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Carqueja collected in Huancayo, Junin, and 145 + 15 g male rats. Interventions: Intestinal tumors were induced by weekly subcutaneous injection of DMH for 22 weeks at 20 mg/kg. Six groups were formed: Group 1 saline, Group 2 100 mg /kg EEBG; Group 3 DMH; Group 4 DMH plus 100 mg/kg EEBG; Group 5 DMH plus 250 mg/kg EEBG; Group 6 DMH plus 500 mg/kg EEBG. Finally, blood samples were drawn to determine malondialdehyde and nitric oxide level. Main outcome measures: Chemoprotection. Results: Histopathology showed chemoprotection in groups treated with EEBG versus the group without treatment, showing better chemoprotection at 500 mg/kg doses where cancer was poorly differentiated and presenting adenomas, compared with adenocarcinoma in situ and adenocarcinoma respectively at 250 mg/kg and 100 mg/kg doses. Lipoproteins oxidation potential was reduced in groups treated with EEBG compared to those untreated especially with the 500 mg/kg dose; nitric oxide levels also decreased more with 500 mg/kg dose. Conclusions: Baccharis genistelloides ethanol extract has chemoprotective effects on 1,2-dimethylhydrazine-induced rodent’s colon cancer.